EKSPLANASI MINAT BELI: EFEK CONTENT MARKETING TERHADAP KEPUTUSAN PEMBELIAN - Sjahruddin, Herman; Nasrullah, Nasrullah; Masekken, Viola Pricilia; Saputra, Muh.Gilang Rezky; Samosir, Andrian; Makkarumpa, Andi Sultan Yusuf; Fadilla, Nila (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
The tight competition in the e-commerce business has resulted in the importance of innovation in controlling market share. This research seeks to explain the role of purchase intention as an intervening in testing the effect of content marketing in improving purchasing decisions. A cross-sectional approach is used with the unit of analysis being students of private universities in Makassar City who use Shopee e-commerce. The sample was drawn randomly based on predetermined criteria by utilising the Roscoe Sampling method (1975) through multiplying the number of variables (3) by the minimum sample size (30) resulting in a total sample of 90 units of analysis data. Data testing was conducted by utilising structural equation analysis, through Partial Least Square 3.0. The findings of this study indicate that the more attractive the content marketing offered on a product, the higher (intense) the purchase decision is made through the high purchase interest